Clinical characteristics of myelin-oligodendrocyte glycoprotein antibody-positive pediatric autoimmune encephalitis without demyelination: A case series - Song, Xiaojie; Ma, Jiannan (Frontiers in Immunology, 2022)
Purpose To facilitate the identification of myelin-oligodendrocyte glycoprotein (MOG) antibody-associated diseases in pediatric autoimmune encephalitis without demyelination, we explored the clinical characteristics of patients having MOG antibody-positive pediatric autoimmune encephalitis without demyelination in Children’s Hospital of Chongqing Medical University, China. Methods We reviewed patients’ medical records from January 2019 to June 2022 and retrospectively analyzed clinical manifestations, brain magnetic resonance imaging (MRI) findings, laboratory findings, treatments and outcomes of children with autoimmune encephalitis who tested positive for the MOG antibody in serum but for whom demyelination was not detected on MRI. Results Eighteen patients (6 boys, 12 girls; median age: 103.2 (range: 36–160) months) were included: 15 tested positive for the MOG antibody in both serum and cerebrospinal fluid (CSF); three tested positive only in serum. The most common clinical symptoms were altered mental status (18/18), fever (16/18), headache (14/18), seizures (6/18) and focal neurologic deficits (5/18). All patients had CSF pleocytosis (median count: 74/µL, range: 14–380/µL); five patients had elevated CSF protein levels (median: 0.85 g/L, range: 0.53–1.48 g/L) simultaneously. CSF glucose levels were normal in all patients. Abnormal electroencephalogram (EEG) results were found in 12 patients: generalized or focal slowing (9/12), focal epileptic discharges (2/12), and generalized slowing and focal epileptic discharges (1/12). Twelve of the 18 patients showed hyperintense T2-weighted lesions on brain MRI in the cortex (6), basal ganglia (5), thalamus (3), cerebellum (4), and brainstem (2). All patients received immunotherapy and had favorable outcomes at discharge (modified Rankin scale score: <2). Three children relapsed once; however, all children had good outcomes at the last follow-up. Conclusion MOG antibody-positive pediatric autoimmune encephalitis without demyelination is mainly characterized by long-term fever, altered mental status, headache, mild-to-moderate increase in cell count in the CSF, and normal or abnormal brain MRI, which may involve any part outside the white matter without specificity. All patients with MOG antibody-positive pediatric autoimmune encephalitis without demyelination had favorable outcomes after immunotherapy, while a few patients relapsed once.